Bilateral Arrangement of Temporary Labor Migration : Lessons from Korea’s Employment Permit System - Cho, Yoonyoung; Denisova, Anastasiya; Yi, Soonhwa; Khadka, Upasana (World Bank, Washington, DC, 2018)
The number of individuals who have crossed borders has mushroomed over recent years. The phenomenon of international migration, however, is heterogeneous in terms of the underlying motives and aspirations of migrants. Forced international migrants are involuntarily displaced refugees who flee conflict, violence, or persecution across an international border. Voluntary migrants can additionally be classified into two categories: (i) temporary labor migrants who migrate for economic reasons for a fixed duration of time, and (ii) immigrants who move with the intention of changing their country of residence, due to factors such as wanting to reunite with family or to benefit economically. Bilateral labor agreements (BLAs) between sending and receiving countries are institutional tools designed to facilitate migratory flows and maximize the potential benefits of temporary international migration for all concerned. This study focuses on the employment permit system (EPS) in Korea, a temporary migration program for low-skilled workers considered a good global practice among efforts toward the goal of co-development - that is, the mutual benefit of both sending and receiving nations. The EPS has accomplished several remarkable achievements, including a drastic reduction in migrants’ cost burden, enhanced transparency, reduction in the share of workers overstaying, and improved access to worker protection. The process used to match employers and temporary labor migrants also merits significant improvement.